2004
DOI: 10.2105/ajph.94.5.852
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Firearms: A California Statewide Survey

Abstract: Objectives. We assessed the prevalence and correlates of adolescents’ reports regarding firearms in their homes, of their own, of close friends, and of same-aged peers. Methods. Random-digit-dialed interviews were conducted with 5801 adolescents as part of the California Health Interview Survey. Results. One fifth (19.6%) of California adolescents reported having a firearm in their homes; few (3.0%) reported having their own gun. Characteristics associated with having one’s own gun and with perceptions regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
3
12
1
Order By: Relevance
“…Firearms are present in the homes of between one fifth and one third of American children and adolescents (DuRant et al, 2007; Forbis et al, 2007; Schuster, Franke, Bastian, Sor, & Halfon, 2000; Sorenson & Vittes, 2004). Analyzing data from the 1994 National Health Interview Survey and its Year 2000 objectives supplement, Schuster and colleagues found that 35% of homes with children younger than age 18 years contained at least one firearm (Schuster et al, 2000); more recently, Coyne-Beasley, Miles, Lees, Proescholdbell, and Ford (2012) reported that 40% of North Carolina homes with children between the ages 0 and 18 surveyed in 2008 contained at least one firearm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Firearms are present in the homes of between one fifth and one third of American children and adolescents (DuRant et al, 2007; Forbis et al, 2007; Schuster, Franke, Bastian, Sor, & Halfon, 2000; Sorenson & Vittes, 2004). Analyzing data from the 1994 National Health Interview Survey and its Year 2000 objectives supplement, Schuster and colleagues found that 35% of homes with children younger than age 18 years contained at least one firearm (Schuster et al, 2000); more recently, Coyne-Beasley, Miles, Lees, Proescholdbell, and Ford (2012) reported that 40% of North Carolina homes with children between the ages 0 and 18 surveyed in 2008 contained at least one firearm.…”
mentioning
confidence: 99%
“…Although some data are available (Coyne-Beasley et al, 2012; DuRant et al, 2007; Ikeda, Dahlberg, Kresnow, Sacks, & Mercy, 2003; Schuster et al, 2000; Sorenson & Vittes, 2004), there is still limited understanding of the extent to which firearm ownership, reasons for owning, and storage practices vary by sociodemographic factors and how reasons for ownership relate to storage practices in homes with children. Differences in race/ethnicity and socioeconomic status (SES) are reported in multiple domains of health-related risk behaviors (Myers, 2009), and such differences may exist also in firearm ownership and storage practices.…”
mentioning
confidence: 99%
“…Previous work using the CHIS survey found that a lower proportion of CHIS respondents reported smoking cigarettes, drinking alcohol, or using drugs than did respondents to the California Student Survey, a legislatively mandated survey of 7th, 9th, and 11th grade students from a representative sample of public and private secondary schools in California. 62 Whether responses about risk taking behavior around guns in our survey is similarly low is not known.…”
Section: Discussionmentioning
confidence: 85%
“…8 Readers interested in prevalence data and multivariate analyses of the adolescents' responses about whether there is a gun in the home, as well as whether the teen has his or her own gun, close friends have a gun in their home or of their own, and perceptions of peers' gun ownership, are referred to Sorenson and Vittes (2004). the 67 respondent pairs in which the adolescent lived with neither parent, the 25 respondent pairs in which the adolescent was described as living with one married parent, and the 5 pairs for which living arrangements were not ascertained.…”
Section: Discussionmentioning
confidence: 99%